1977
DOI: 10.1111/1523-1747.ep12491663
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Epidermal Layers of the Newborn Rat

Abstract: A method is presented for the separation of epidermal strata by the successive elimination of either the basal or basal and spinous cells with 0.24 M NH4Cl at pH 9.5. Histologic evidence suggests that the residual epidermal strata obtained after incubation of the skin with NH4Cl are reproducible; hence, this technique circumvents loss of granular layer histidine-rich protein inherent with trypsin separation and provides an effective procedure for biochemical analysis of arginine-rich and lysine-rich proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A single sample of cell envelopes was isolated from a pool of epidermal sheets obtained by this means. Samples of epidermis from skin obtained post mortem were prepared free of dermis by treatment with 0.24 M-NH4Cl at pH 9.5 as described [16]. Cell envelopes were isolated from epidermis, callus and psoriatic scales by gentle overnight stirring at room temperature in 0.025 M-Tris/HCl buffer, pH 9, contaihing 8 M-urea, 2 mM-2-mercaptoethanol and 0.2 % SDS, followed by centrifugation for 20 min at 750 g. The insoluble crude envelopes were freed of remaining soluble impurities by washing three times for 2 h with the same buffer mixture at room temperature and three times for 5 min with this mixture at 100 'C.…”
Section: Methodsmentioning
confidence: 99%
“…A single sample of cell envelopes was isolated from a pool of epidermal sheets obtained by this means. Samples of epidermis from skin obtained post mortem were prepared free of dermis by treatment with 0.24 M-NH4Cl at pH 9.5 as described [16]. Cell envelopes were isolated from epidermis, callus and psoriatic scales by gentle overnight stirring at room temperature in 0.025 M-Tris/HCl buffer, pH 9, contaihing 8 M-urea, 2 mM-2-mercaptoethanol and 0.2 % SDS, followed by centrifugation for 20 min at 750 g. The insoluble crude envelopes were freed of remaining soluble impurities by washing three times for 2 h with the same buffer mixture at room temperature and three times for 5 min with this mixture at 100 'C.…”
Section: Methodsmentioning
confidence: 99%
“…Postnatal back skins were collected from suckling mice at 2∫2, 6∫2, 18∫2, and 72∫2 h after birth. The epidermis was obtained by the alkaline ammonium chloride method of Walker et al (13) under cooling with ice, washed with ice cold PBS, and stored at ª76aeC until use.…”
Section: Animals and Tissue Samplesmentioning
confidence: 99%
“…may be correct. As Walkcr et al indicated in their recent paper ( 17), the incubation of rat skin in a butl er solution containing 0.5 '1-trypsin caused dissolution of the usual type of keratohyalin granule. lf this is correct and DH D are resistant to trypsin digestion.…”
Section: Discussionmentioning
confidence: 88%